Assessing the Relationship between Neurocognitive Performance and Brain Volume in Chronic Moderate–Severe Traumatic Brain Injury - Konstantinou, Nikos; Pettemeridou, Eva; Seimenis, Ioannis; Eracleous, Eleni; Papacostas, Savvas S.; Papanicolaou, Andrew C.; Constantinidou, Fofi (Frontiers in Neurology, 2016)
Objectives. Characterize the scale and pattern of long-term atrophy in grey matter (GM), white matter (WM) and cerebrospinal (CSF) in chronic moderate-severe traumatic brain injury (TBI) and its relationship to neurocognitive outcomes. Participants. The TBI group consisted of 17 males with primary diagnosis of moderate-severe closed head injury. Participants had not received any systematic, post-acute rehabilitation and were recruited on average 8.36 years post-injury. The control group consisted of 15 males matched on age and education. Main measures. Neurocognitive battery included widely used tests of verbal memory, visual memory, executive functioning, and attention/organization. GM,WM, and CSF volumes were calculated from segmented T1-weighted anatomical MR images. Voxel-based morphometry was employed to identify brain regions with differences in GM and WM between TBI and control groups. Results. Chronic TBI results in significant neurocognitive impairments, and significant loss of GM and WM volume, and significant increase in CSF volume. Brain atrophy is not widespread, but it is rather distributed in a fronto-thalamic network. The extent of volume loss is predictive of performance on the neurocognitive tests. Conclusion. Significant brain atrophy and associated neurocognitive impairments during the chronic stages of TBI support the notion that TBI results in a chronic condition with lifelong implications.